Photoinduced Electron Transfer within a Zinc Porphyrin–Cyclobis(paraquat‐p‐phenylene) Donor–Acceptor Dyad. Issue 45 (26th September 2014) - Fathalla, Maher; Barnes, Jonathan C.; Young, Ryan M.; Hartlieb, Karel J.; Dyar, Scott M.; Eaton, Samuel W.; Sarjeant, Amy A.; Co, Dick T.; Wasielewski, Michael R.; Stoddart, J. Fraser
Abstract Understanding the mechanism of efficient photoinduced electron‐transfer processes is essential for developing molecular systems for artificial photosynthesis. Towards this goal, we describe the synthesis of a donor–acceptor dyad comprising a zinc porphyrin donor and a tetracationic cyclobis(paraquat‐p‐phenylene) (CBPQT4+) acceptor. The X‐ray crystal structure of the dyad reveals the formation of a dimeric motif through the intermolecular coordination between the triazole nitrogen and the central Zn metal of two adjacent units of the dyad. Photoinduced electron transfer within the dyad in MeCN was investigated by femtosecond and nanosecond transient absorption spectroscopy, as well as by transient EPR spectroscopy. Photoexcitation of the dyad produced a weakly coupled ZnP+.–CBPQT3+. spin‐correlated radical‐ion pair having a τ=146 ns lifetime and a spin–spin exchange interaction of only 0.23 mT. The long radical‐ion‐pair lifetime results from weak donor–acceptor electronic coupling as a consequence of having nine bonds between the donor and the acceptor, and the reduction in reorganization energy for electron transfer caused by charge dispersal over both paraquat units within CBPQT3+..